On current issues of economic development of the Republic of Belarus: status and ideas - Myasnikovich, Mikhail V. (Journal of the Belarusian State University. Economics, 2018)
The problematic issues of economic policy of Belarus are covered. The emphasis is made on the peculiarities of the Program of socio-economic development of the Republic of Belarus for the period 2016 –2020. The importance of the development of the scientific sphere, in particular, the conduct of fundamental research, as well as the need to determine the status of the National Academy of Sciences of Belarus, is substantiated. The problem field of the investment policy in the country is outlined, the prerequisites, the state and prospects for economic integration are indicated. It is given the evaluation of the challenges and prospects of the Belarusian-Chinese cooperation. The relevance of Belarusian participation in the project “Economic belt of the Silk Road” is being proved.